Fabricação de implantes intraorbitais via processamento digital de luz (DLP) - Almeida, Ycaro Breno Alves de (2025)
Several clinical situations require surgeries that reduce the volume of the orbital cavity, making it necessary to replace this volume to preserve the patient's aesthetics. There is still no consensus on the ideal material for this. A promising alternative is the Biosilicate implant, already clinically tested. However, its fabrication by melt-solidification limits the creation of complex shapes. In this context, the digital light process (DLP) emerges as a ceramic additive manufacturing technique that offers high surface quality and dimensional accuracy. Therefore, the objective of this study was to manufacture, in a novel way, intraorbital implants based on Biosilicate using the DLP technique. Biosilicate was successfully obtained and characterized using differential scanning calorimetry (DSC) and X-ray fluorescence (XRF) analysis. The effects of milling with and without solvent were demonstrated through dilatometric analyses. Sintering can be performed at 950°C without significant foaming, preserving the integrity of the printed structure. With the Biosilicate in hand, the suspension was prepared for DLP printing, aiming for high solids concentration and good stability. Rheological studies with different solids (30, 40, and 50% vol) and dispersant (0.1–5% vol) contents indicated that the formulation with 40% solids and 5% dispersant, although presenting a viscosity slightly above the ideal value, was considered suitable and chosen for printing the intraorbital implants. The implants were successfully printed, resulting in defect-free, gyroid-like parts after the thermal debinding and sintering processes. In vitro bioactivity tests in simulated body fluid (SBF) showed the formation of hydroxycarbonate apatite (HCA) after only 6 hours of immersion.